Analysis of an Extensible Teaching Mode for Cultivating College Students into Innovative Talents - Li, Changliang; Liu, Hui (International Journal of Emerging Technologies in Learning (iJET), 2021)
The competition between countries is essentially the competition of innovative talents. However, China now faces multiple problems in the cultivation of innovative talents: the talents are weak in innovation ability; the high-level innovative talents are not sufficient; neither the quality or level of talents fully meet the demand of social and economic development. As a result, it is urgent for colleges to renovate the cultivation mode of innovative talents. Focusing on the cultivation of innovative talents majoring in architectural design, this paper thoroughly analyzed the extensible teaching mode for cultivating college students into innovative talents. Firstly, a questionnaire survey on relevant issues was carried out among employers and college graduates. The survey results revealed several problems with the innovative talent training in Chinese colleges, namely, the irrational curriculum design, the narrow scope of training objectives, and the lack of diverse teaching methods. Results verified, the employers are not highly satisfied with the innovative talents, especially the newly graduated ones. These problems are attributable to the weak professional development ability, poor teamwork ability, and insufficient innovation ability. To solve these problems, the authors analyzed and expounded the extensible teaching mode for the cultivation of innovative talents from four aspects: teaching content scope, teaching methods, teaching space, and appraisal. The research findings enrich the evidences of innovative talent training in Chinese colleges, providing a reference for improving the training quality of innovative talents.